Ethylene conversion to higher hydrocarbon over copper loaded BZSM-5 in the presence of oxygen - Mat, Ramli; Saidina Amin, Nor Aishah; Ramli, Zainab; W. Abu Bakar, W. Azelee (2006)
The successful production of higher hydrocarbons from methane depends on the stability or the oxidation rate of the intermediate products. The performance of the BZSM-5 and modified BZSM-5 catalyst were tested for ethylene conversion into higher hydrocarbons. The catalytic experiments were carried out in a fixed-bed micro reactor at atmospheric pressure. The catalysts were characterized using XRD, NH3-TPD and IR for their structure and acidity. The result suggests that BZSM-5 is considered a weak acid. The introduction of copper into BZSM-5 improved the acidity of BZSM-5. The conversion of ethylene toward higher hydrocarbon is dependent on the acidity of the catalyst. Only weaker acid site is needed to convert the ethylene to higher hydrocarbons. Loading of Cu on BZSM-5 improved the selectivity of higher hydrocarbons especially at lower percentage. The reactivity of ethylene is dependent on the number of acidity as well as the presence of metal on the catalyst surface. Cu 1%BZSM-5 is capable of converting ethylene to higher hydrocarbons. Balances between metal and acid sites influence the performance of ethylene conversion and higher hydrocarbon selectivity. Higher loading of Cu leads to the formation of COx.